Compatibility and Mechanical Performance of High-Strength Self-Compacting Concrete Produced with Recycled Glass Powder - Taher Muntadher J.; Al-Attar Tareq S.; Al-Adili Aqeel S. (Civil and Environmental Engineering)
Due to its large activity and raw material use, construction offers great recycled material potential. Demolition and construction waste affect the cycle. Broken window glass powder can replace self-compacting concrete due to its pozzolanic properties. This study will quantify high-strength self-compacting concrete’s compatibility and mechanical characteristics (HSSCC) with varied amounts of waste glass powder. This study explored using limestone powder with 0.46 µm waste glass powder (WGP) as a filler in self-compacting concrete (SCC) mixtures. Waste glass powder (WGP) was tested as limestone filler powder replacements at 25%, 50%, 75%, and 100% by weight. Waste glass powder (WGP) was tested on compatibility with self-compacting concrete (SCC). This was done via slump flow, L-box, T500, and V-funnel testing. Furthermore, compressive, splitting tensile, and flexural strengths were to be assessed. SCC with WGP at varied replacement percentages had good flowability, passing ability, and viscosity in newly mixed concrete. Due to its filler effect and pozzolanic activity, WGP improves self-compacting concrete (SCC) compatibility and mechanical qualities. The efficiency of WGP replacement was substantially higher at 50%, resulting in a more marked influence on enhancement, particularly among those in older age groups.